Strategi Guru Tahsin Di Kelas Rendah Dalam Meningkatkan Motivasi Belajar Membaca Al-Qur’an Peserta Didik - Ayu, Herdiansyah; Sultansyah, Panji; Rahman, Abdul (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This research is in the background by some students in the lower grades of Aisyiyah Superior Elementary School Taman Harapan Curup have low motivation to learn to read the Quran. This research is a qualitative descriptive case study research. Data collection techniques through observation, interviews, and documentation. Then the data analysis technique uses data reduction, data presentation, and conclusion or verification as well as data credibility test using source triangulation, techniques (methods). The results of this study concluded that: (1) The motivation to learn to read the Qur'an of students who have low motivation at SD Unggulan 'Aisyiyah Taman Harapan Curup is characterized by their low learning ability such as difficulty in proclaiming hijaiyah letters, having poor behavior such as making noise in class, not paying attention to lessons, difficulty when reading while writing and accompanied by the rhythm of songs,  have disturbances in the physical, psychological, and learning environment. (2) The strategy of tahsin teachers in the lower grades is to educate by being guided by the goals of tahsin learning, encouraging physical and psychological activities of students such as learning while playing, giving more special attention by collaborating with homeroom teachers and parents, being consistent in developing assessments on cognitive, affective, and psychomotor aspects.